Analisis Peran Green Sukuk dalam Mendorong Pembangunan Infrastruktur Berkelanjutan yang Ramah Lingkungan di Indonesia - Meitria Cahyani; M.Bagus Saputro; Muhammad Azrul Amirullah; Andini Rachmawati; Yusuf Al Manaanu; Arif Dian Santoso (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Realizing massive and equitable infrastructure development requires significant funding, while public demand for Sharia-compliant financial products is also increasing. This issue has prompted the government and relevant institutions to create Sharia-compliant financial instruments that can inject significant funding into these projects. One such Sharia-compliant financial instrument is Green Sukuk. Green Sukuk is an innovative, environmentally friendly form of financing. This study aims to analyze the influence of Green Sukuk on the massiveness of national infrastructure development through a literature review approach. This article takes a descriptive approach and utilizes content analysis as its research methodology. This method was chosen based on the need to adhere to existing theoretical foundations as a guide, ensuring that the focus of the writing aligns with the reality on the ground. The results show a significant relationship between Green Sukuk issuance and the level of massiveness of national infrastructure development. This study demonstrates the influence of Green Sukuk as a significant source of financing for the massiveness of infrastructure development in Indonesia.